SAGA reloaded: towards a generic platform for developing cooperative applications - Fonseca, Benjamim (2009)
Groupware specification and development has always been a complex task, requiring special attention to issues such as notification of cooperative actions and ensuring consistency of shared data. Some years ago SAGA was developed as a framework to build groupware applications based on a set of core web services that provide the most common cooperative functionalities. Despite its potential, the last few years brought some technological developments that placed new challenges. This paper presents a new generation of the SAGA platform that adds to the original framework features that emerged recently, namely the regulation of social interaction, incorporation of new communication technologies, connectors to several external services and interaction environments, and the addition of contextual information.